Tinjauan Terhadap Materi dan Kedudukan Ketetapan MPR/MPRS Staatsgrundgesetz - Indrati, Maria Farida (Indonesian Journal of International Law, 2005)
The Amandment to the 1945 Constitution of the Republic of Indonesia, especially the Article 3 and 6, has an impact on the existence of Decree of the People’s Consultative Assembly of the Republic of Indonesia. The new article 3 stated that: (1) The People’s Consultative Assembly of the Republic of Indonesia has the authority to amend and to enact the Constitution; (2) The People’s Consultative Assembly shall inaugurate the President and/or the Vice President; (3) The People’s Consultative Assembly may only remove the President and/or the Vice President during his/her term of office in accordance with the constitution. Article 6A: (1) The President and the Vice President shall be elected as a single ticket directly by the people. Based on the two Articles, the President of the Republic of Indonesia in the future is not mandatory of the Peope’s Consultative Assembly and he/she shall not be accountable to the People’s Consultative Assembly.